2018
DOI: 10.1002/joc.5672
|View full text |Cite
|
Sign up to set email alerts
|

Winter hoar frost conditions on Swedish roads in a warming climate

Abstract: As one of the most common reasons for slippery roads in wintertime, hoar frost can reduce surface friction and affect traffic safety. The risk of winter road hoar frost is subjected to changes in the warming climate. A better understanding of these changes could lead to improved forecasting of hoar frost risk and provide information to policymakers in making climate adaptation strategies. In this work, the decadal variation in winter road hoar frost risk between 2000 and 2016 in Sweden was examined by using in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Hu et al . () showed that the volume of water vapour transported from the southwest increased in a warming climate, which may result in more occurrences of warm air advection. However, based on the above analysis, some occurrences of warm air advection may not lead to an increase in temperature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hu et al . () showed that the volume of water vapour transported from the southwest increased in a warming climate, which may result in more occurrences of warm air advection. However, based on the above analysis, some occurrences of warm air advection may not lead to an increase in temperature.…”
Section: Discussionmentioning
confidence: 99%
“…RWIS does not record the occurrence of hoar frost directly, so the above variables were used to infer an occurrence of hoar frost. For the purposes of this study, a hoar frost event occurs when RST ≤ 0 C and RST < T d (Takle, 1990;Karlsson, 2001) for at least 2 hr (no precipitation should be detected during the same period) same definition as the one used by Hu et al (2018). A day with a hoar frost event detected is called a hoar frost risk day.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Fewer zero-crossings may also lead to fewer days with slippery conditions, however, this connection is less certain (Šidlauskaitė and Kažys, 2019). Hu et al (2018) argue that increasing temperatures alone are not sufficient to assess such changes. In addition, humidity data (e.g., dew-point temperature) is required to assess changes in slippery conditions.…”
Section: Implications Of Changes In Dzcsmentioning
confidence: 99%
“…Projected changes in days with zero-crossings (DZCs) have been requested by several user groups in Norway (Hanssen-Bauer et al, 2017b). For certain applications, zero-crossings of the ground temperature are of interest; such applications include the development of icy conditions and hoar frost (Hu et al, 2018), and snow insulation effects on plants (Tierney et al, 2001;Kreyling and Henry, 2011). The topic of this study is, however, zero-crossings of the two-metre air temperature.…”
Section: Introductionmentioning
confidence: 99%